2020
DOI: 10.3390/su12083207
|View full text |Cite
|
Sign up to set email alerts
|

Industry 4.0—Awareness in South India

Abstract: Industry 4.0 (I4.0) approaches, frameworks, and technologies have gained an increasing relevance in order to gain sustainable and competitive advantages for industrial enterprises and for small and medium enterprises (SMEs), as well. Contrary to previous studies, which are mainly focused on companies, we conducted a questionnaire-based survey on inhabitants, in an attempt to examine general awareness about I4.0 concepts, in the region of South India. Our findings revealed a rather poor informational level of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
1
14
0
2
Order By: Relevance
“…Safar et al [12] To examine opinions and attitudes of inhabitants of South India with a survey method; to emphasize insufficient knowledge of the fourth industrial revolution and industry 4.0 of the potential workforce and to suggest education and requalification is necessary…”
Section: Reference Study Aims Our Contributionsmentioning
confidence: 99%
“…Safar et al [12] To examine opinions and attitudes of inhabitants of South India with a survey method; to emphasize insufficient knowledge of the fourth industrial revolution and industry 4.0 of the potential workforce and to suggest education and requalification is necessary…”
Section: Reference Study Aims Our Contributionsmentioning
confidence: 99%
“…Another very important social aspect of such a smart environment is how intelligent machines will affect the labour market (Eberhard et al 2017;Dallasega et al 2019Woschank et al 2020). This topic can be being examined from two perspectives, firstly by describing requirements towards workers in I4.0 (Eberhard et al 2017;Safar et al 2020), secondly by examining the standpoint of workers and their outlook or current state of mind (Eberhard et al 2017;Wolter et al 2015). We argue, that unless a reasonable level of awareness and basic knowledge of Industry 4.0 related concepts and inevitable parts is reached, it will be hard to successfully move towards a smart environment, especially in the case of less developed regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fig. 11.4The answers to the questions Q19, Q20-Q25 (Adapted fromSafar et al [2020]) …”
mentioning
confidence: 99%
“…(i) Exports are a major focus of Indian Engineering industries, therefore, for the products to be competitive Industry 4.0 implementation cannot be ignored, (j) In a study which explored the awareness of Industry 4.0 in south India, it was found that term " Mass Customization" was not known to 60 % responding citizens and "Industry 4.0" was not known to 49.6%. This suggests general awareness about Industry 4.0 in Indian society is very low towards [30]. Therefore, there is a need for a study which analyses the impact of Industry on Indian Engineering Industries.…”
Section: Related Workmentioning
confidence: 99%